How 2D semiconductors could extend Moore’s law - Li, Ming-Yang; Su, Sheng-Kai; Wong, H.-S. Philip; Li, Lain-Jong (Nature (London), 2019)
Incredibly thin transistors could deliver even more powerful computers if three research challenges can be solved, argue Ming-Yang Li and colleagues. Incredibly thin transistors could deliver even more powerful computers if three research challenges can be solved, argue Ming-Yang Li and colleagues. A working electronic device made by stacking atom-thick layers of 2D materials